High efficiency integrated III-V-nitride solar cells on silicon-based substrates - Leong, Nelvin Yurong (2018)
Solar energy has a huge potential to reduce the world’s reliance on fossil fuels. However, due to the excess current wasted by the Ge sub-cell, the energy conversion efficiency of a typical lattice-matched triple junction (InGaP/Ga(In)As/Ge) photovoltaic (PV) cell can only reach 41% under concentrated suns. The addition of a 1-eV sub-cell between the Ga(In)As and Ge sub-cell has been predicted to achieve an energy conversion efficiency of 50% under concentrated suns. Thus, in this work, high efficiency PV cells were grown on a silicon substrate to increase the conversion efficiency and reduce the PV production cost. We demonstrated a 1-eV GaNAsSb PV cell on a Si-Ge/Si substrate using molecular beam epitaxy (MBE). The cell exhibited the lowest ever reported Eg/q-VOC value of 0.50 eV. This indicates that the 1-eV GaNAsSb layer has a high crystalline quality with a long carrier lifetime. The growth conditions of the GaNAsSb layer were optimised by varying the As/Ga ratio, growth temperature, annealing temperature and annealing duration. The As/Ga ratio was found to affect the concentration of arsenic anti-site defects and nitrogen-related defects. On the other hand, the growth temperature was found to affect nitrogen phase separation or segregation. We found that annealing at 700°C for 5 mins can improve the performance of the PV cell by removing non-radiative defects. However, annealing at a temperature exceeding the optimal temperature of 700°C for more than 5 mins severely deteriorates the PV cell performance. Previous modelling works assumed an ideal quantum efficiency for all the sub-cells. However, the experimental quantum efficiency of 1-eV GaNAsSb was well below the ideal condition. Modelling work was carried out to optimise the bandgap energies of the top two sub-cells using the published experimental quantum efficiency of InGaP, GaAs, 1-eV GaNAsSb and Ge. The bandgap energies of the bottom two sub-cells were fixed at 1.03 eV and 0.66 eV, which represented the GaNAsSb and Ge sub-cell, respectively. The model showed that the optimised bandgap energy of the first and second sub-cells were 2.00 eV and 1.56 eV, respectively. These bandgap energies are higher compared to the bandgap energies of the top two sub-cells in typical triple junction cells, which are 1.86 eV (InGaP) and 1.42 eV (Ga(In)As), respectively. An increase in the bandgap energy levels in the top two sub-cells allows more light to be transmitted to the third sub-cell. With the optimised bandgap of 2.00/1.56/1.03/0.66 eV in a quadruple junction cell, the energy conversion efficiency at the one-sun condition can be increased to 38.8%. The energy conversion efficiency can be boosted to 49% under the 500 suns condition. Under this configuration, a one-sun short circuit current density of 11.8 mA/cm2, an open circuit voltage of 3.65 V and a fill factor of 90% can be achieved in a photovoltaic cell. We also grew and fabricated 1.56 eV PV cells using Al0.11GaAs on a Si-Ge/Si substrate. The material quality of the AlGaAs layer was optimised by varying the V/III ratio, growth temperature and base thickness to obtain maximum performance in the PV cell. The substrate temperature was found to affect the group III site vacancies while the V/III ratio was found to affect the VAs, GaAs and AsGa. Both parameters were also found to affect the incorporation of oxygen-related complexes. The AlGaAs PV cell grown on a Si-Ge/Si substrate seems to favour a lower substrate temperature of 630˚C rather than a higher substrate temperature of 680°C on a GaAs substrate. The AlGaAs PV cell grown on a GaAs substrate has the best material quality at a substrate temperature of 680˚C and a V/III ratio of 15. This growth process is important in showing the potential of the 1.56 eV AlGaAs PV cell on a Si-Ge/Si substrate and future integration with a 1-eV GaNAsSb PV cell as well as the 2.0 eV sub-cell (AlGaInP) and Ge sub-cell. The four materials are closely lattice-matched with GaAs and can be grown directly on the Si-Ge/Si.